The effects of monetary policy on unemployment dynamics under model uncertainty: evidence from the US and the euro area - Carlo Altavilla; Matteo Ciccarelli (European Central Bank (ECB), 2009)
This paper explores the role that the imperfect knowledge of the structure of the economy plays in the uncertainty surrounding the effects of rule-based monetary policy on unemployment dynamics in the euro area and the US. We employ a Bayesian model averaging procedure on a wide range of models which differ in several dimensions to account for the uncertainty that the policymaker faces when setting the monetary policy and evaluating its effect on real economy. We find evidence of a high degree of dispersion across models in both policy rule parameters and impulse response functions. Moreover, monetary policy shocks have very similar recessionary effects on the two economies with a different role played by the participation rate in the transmission mechanism. Finally, we show that a policy maker who does not take model uncertainty into account and selects the results on the basis of a single model may come to misleading conclusions not only about the transmission mechanism, but also about the differences between the euro area and the US, which are on average essentially small.
Keywords: C11; E24; E52; E58; 330; Bayesian model averaging; Model uncertainty; monetary policy; Taylor rule; Unemployment gap; Geldpolitik; Taylor-Regel; Geldpolitische Transmission; Entscheidung unter Unsicherheit; Natürliche Arbeitslosenquote; Makroökonometrie; Wirkungsanalyse; Arbeitslosigkeit; USA; EU-Staaten